Edukasi Kesehatan dan Suplementasi Vitamin di SDN 1 Bunigeulis dan SDN Tundagan Kabupaten Kuningan - Juju Jumiati; Wawang Anwarudin; Ari Abdullah Safari; Oman Hadiana; Tedi Arisandi (Universitas Baiturrahim, 2026)
Micronutrient deficiencies, including vitamin deficiencies, remain a significant public health challenge in rural areas of Indonesia, particularly among elementary school children. Limited dietary diversity and low nutritional literacy increase children's vulnerability to vitamin deficiencies, which may adversely affect immune function, learning concentration, and physical growth. This community service program aimed to enhance students' understanding of the importance of adequate vitamin intake and to provide vitamin supplementation as a preventive measure. The program was conducted at SDN 1 Bunigeulis, involving 58 students, and SDN Tundagan, involving 54 students, with a total of 112 participants. The activities were implemented through three stages: (1) development of educational materials on vitamins found in fruits and vegetables as well as vitamins that support immune health, (2) delivery of interactive nutrition education sessions, and (3) distribution of vitamin supplements. Educational and communicative methods were employed, utilizing visual approaches and engaging educational games tailored to elementary school students. Program effectiveness was evaluated through observations of all 112 participants. The results indicated that 91.9% of students actively participated in the educational sessions, while 77.6% were able to correctly identify the functions and dietary sources of vitamins. Furthermore, both teachers and students responded positively to the vitamin supplementation program, and no adverse effects were reported. These findings demonstrate that the program was effective in improving students’ nutritional awareness and may serve as a practical and scalable intervention model for elementary schools in rural communities.